A reciprocal test of Darwin's naturalization hypothesis in two mediterranean‐climate regions. Issue 9 (24th July 2015) - Park, Daniel S.; Potter, Daniel
Abstract Aim Regions with a mediterranean climate are among the most species‐rich regions in the world. They are also among the regions with the greatest number of non‐native invasive species. However, not all introduced species become invasive. Previously, we found that non‐native Asteraceae closely related to native species are more likely to establish and spread in California, USA. We conducted reciprocal studies in another mediterranean‐climate region with high species richness, the Italian Peninsula. Mediterranean Basin invaders in the Astereae mostly originated in temperate North America, whereas the invasive Cardueae of California are primarily from the Mediterranean Basin. Location The Mediterranean Basin (Italy). Methods Utilizing the first fossil‐calibrated molecular phylogenies of the tribe Astereae, we explored the evolutionary patterns among native and non‐native taxa within this group. To elucidate the mechanisms driving the observed patterns, we modelled the ecological niches of Astereae species on a global scale and examined correlations between ecological similarity and evolutionary relatedness among taxa. Results Not only were invasive taxa highly clustered among natives, they were also more closely related to natives than were non‐invasive introduced taxa. We found that invasive species had higher degrees of niche overlap with native species than did non‐invasive introduced species. Moreover, pairwise niche distance among species was significantly correlated with evolutionary time, indicating that the ecological niche is phylogenetically conserved. Main conclusions The results of our study are consistent with those from our work in California, suggesting that introduced Asteraceae taxa that are closely related to native species are likely to become invasive on both sides of the Atlantic. Furthermore, existing ecological attributes seem to drive these evolutionary patterns. We suggest that potential invaders closely related to natives should be considered as high priorities for management.